Penerapan model pembelajaran kooperatif tipe jigsaw untuk meningkatkan motivasi dan hasil belajar - Gusti Made Adi Widarta (Indonesian Journal of Educational Development, 2020)
This research is a classroom action research that aims to determine the effectiveness of the application of the Jigsaw cooperative learning model can improve student motivation and learning outcomes. The subjects of this study were students of class XI MIPA3 of SMA Negeri 1 Marga in semester 1 of the 2019/2020 academic year, totaling 39 people consisting of 18 male students and 21 female students. The object of research is motivation and learning outcomes of chemistry.Student motivation data were collected using a questionnaire, while learning outcomes data were collected using learning outcomes tests. The data collected was analyzed descriptively qualitatively. This action research is said to have succeeded if it met the following requirements: (1) minimal student motivation in the high category, (2) the average value of minimum daily tests of KKM = 68, and classical learning completeness of at least 85%. Before the study was conducted the students' motivation was very low, as seen from the assignments not being completed on time, some students arrived late, and in class many students were sleepy. The average value of the previous daily tests was 66.18 and from 39 students it turned out that only 27 people were complete so that classical completeness only reached 69.23%. After conducting classroom action research, inthe first cycle students 'motivation was quite high, the average value of the students daily tests was 69.03, and from 39 students only 32 people were completed so that classical completeness reached 82.05%. In the second cycle the results achieved were high student learning motivation, the average value of daily tests reached 72.68, and of 39 students it turned out that 35 people had reached completeness so that learning completeness classically reached 89.74%. Conclusion: the applicationof a jigsaw cooperative learning model can increase students' motivation and chemistry learning outcomes in two cycles. Penelitian ini adalah penelitian tindakan kelas yang bertujuan untuk mengetahui sejauh mana penerapan model pembelajaran kooperatof tipe jigsaw dapat meningkatkan motivasi dan hasil belajar siswa. Subjek penelitian ini adalah siswa kelas XI MIPA3 SMA Negeri 1 Marga semester 1 tahun pelajaran 2019/2020 yang berjumlah 39 orang terdiri dari 18 orang laki-laki dan 21 orang perempuan. Objek penelitian adalah motivasi dan hasil belajar kimia. Data motivasi siswa dikumpulkan menggunakan kuesioner, sedangkan data hasil belajar dikumpulkan menggunakan tes hasil belajar. Data yang terkumpul dianalisis secara deskriptifkualitatif. Penelitian tindakan kelas ini dikatakan sudah berhasil bila memenuhi syarat-syarat: (1) motivasi siswa minimal tinggi, (2) nilai rata-rata ulangan harian minimal sebesar KKM=68, dan ketuntasan belajar klasikal minimal 85%. Sebelum dilakukan tindakan motivasi belajar siswa sangat rendah, terlihat dari tugas-tugas tidak diselesaikan tepat waktu, beberapa siswa datang terlambat, dan di kelas siswa banyak yang mengantuk. Nilai rata-rata ulangan harian sebelumnya adalah 66,18 dan dari 39 orang siswa ternyata hanya 27 orang dinyatakan tuntas sehingga ketuntasan klasikal hanya mencapai 69,23%. Setelah dilakukan penelitian tindakankelas, pada siklus I motivasi siswa tergolong cukup tinggi, nilai rata-rata ulangan harian siswa 69,03, dan dari 39 orang siswa hanya 32 orang yang dinyatakan tuntas sehingga ketuntasan klasikal baru mencapai 82,05%. Pada siklus II hasil yang dicapai adalah motivasi belajar siswa tinggi, nilai rata-rata ulangan harian mencapai 72,68, dan dari 39 orang siswa ternyata 35 orang sudah mencapai ketuntasan sehingga ketuntasan belajar secara klasikan mencapai 89,74%. Kesimpulan: penerapan model pembelajaran kooperatif tipe jigsaw dapat meningkatkan motivasi dan hasil belajar kimia siswa dalam dua siklus.